PERANAN BUDAYA ORGANISASI SEBAGAI PEMODERASI PADA PENGARUH PERILAKU KEPEMIMPINAN DENGAN KOMITMEN ORGANISASI DAN KOMITMEN ORGANISASI DENGAN KEPUASAN KERJA DAN KINERJA (Studi pada Rumah Sakit Daerah âRAA Soewondoâ Pati) - Murniyati, Endang (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2011)
The purpose of this research is to investigate the effect of leadership behavior to organizational commetment, analyze the organizational culture in moderating the effect of leadership bahavior to organizational commitment, analyze the effect of organizational commitment to job satisfaction, analyze the effect of organizational commitment to performance, analyze the organizational cultur in moderating the effect of organizational commitment to job satisfaction, and analyze organizational culture in moderating the effect of organizational commitment to performance. Research population are 696 persons and the samples taken are 100, sample were taken by purposive sampling. The analyze method used is qualitative by hierarchical regression analysis. The result found is positive influence of leadership behavior to organization commitment; positif influence leadership behavior to organization commitment which is moderated by organization culture; positive influence of organization commitment to job satisfaction; positive influence of organization commitment to performance; positive influence of organization commitment to job satisfaction which is moderated by organizational culture; and positive influence of organization commitment to performance which is moderated by organizational culture.